The Influence of Profitability, Accounting Conservatism, and Leverage on Earnings Quality with Company Size as The Moderating Variable - Jennifer, Miranda; Fahmi, Muhammad; Rusmita, Sari (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
Profit information provides the needs for stakeholders in assesing management’s success and company’s profit targets. This research intends to examine the influence of profitability, accounting conservatism, and leverage on earnings quality, also the moderating role of company size. The study object was conducted at Non-Cyclical Consumer Companies on the BEI from 2018-2022. The research method uses moderated regression analysis using Eviews version 10. The test results show that profitability and accounting conservatism negatively impact earnings quality, while leverage has no effect. Company size is unable to play the moderating role to affect profitability, accounting conservatism, and leverage on earnings quality.